ANALISIS PENGARUH KEPUASAN KERJA DAN KOMITMEN NORMATIF TERHADAP KINERJA KARYAWAN DENGAN TURNOVER INTENTION SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan Departemen Pabrik PT. Eka Dura Indonesia) - Ismahayati Ismahayati; Garnasih Lestari Raden; Fitri Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims determine the effect of job satisfaction and normativecommitment on employee performance with turnover intention as an interveningvariable of employee Factory Staff PT. Eka Dura Indonesia. Populations in the study to143 peoples and sampling technique is using slovin method. So the sample amounts to105 peoples. The datas is testing by instumental testing whit is the validity test, reabilitytest and classic assumption test. The analytical methods of this research is usingdescriptive analysis and path analysis using SPSS 23 for windows. Based on the resulthypothesis test, then the conclusion are: 1) job satisfaction and organizationalcommitment gives negatif effect and significant on turnover intention. 2) job satisfactionand organizational commitment gives positif effect and significant on employeeperformance 3) turnover intention gives negatif effect and significant on employeeperformance, 4) turnover intention has mediate the relationship between job satisfactionand organizational commitment on employee performance.Keywords : Employee Performance; Turnover Intention; Job Satisfaction;Organizational Commitment